Processes of land use change in mining regions - Sonter, L.; Moran, Christopher; Barrett, D.; Soares-Filho, B. (Elsevier, 2014)
© 2014 Elsevier Ltd. All rights reserved. Mining regions undergo abrupt and extensive land use change, the impacts of which pose management challenges for mining companies and regulatory agencies. In this study we investigated 20 years of land use change in Brazil's Iron Quadrangle (QF) mining region. We classified remote sensing images to produce land use maps and conducted a Land Change analysis to investigate the causes and consequences of observed changes. The QF underwent extensive land use change between 1990 and 2010, including deforestation, plantation expansion, urbanization and mine expansion. Comparing our results with those of surrounding non-mining landscapes illustrated important differences. For example, QF contained additional highly profitable land uses, including mining and plantation forestry, which were driven by globalized markets for mineral resources. This finding suggests processes of land use change within mining regions are distinct from those found elsewhere and, as such, land management policies should reflect this. We also hypothesized four generalizations regarding these processes: 1) the direct footprints of mining expands over time, 2) the offsite footprints of mining are extensive and also often expanding, 3) the direct and indirect land used by mines causes environmental and social impacts, some of which are not captured by current management approaches, and 4) the footprints of mining (and associated impacts) are driven by global factors, many of which are uncontrollable by local land holders and regional land management plans and policies. We describe and discuss these generalizations, drawing on published evidence from other mining regions to illustrate both their generality and implications for land management.